2018
DOI: 10.1016/j.aquaculture.2018.04.059
|View full text |Cite
|
Sign up to set email alerts
|

Variation in cultured pearl quality traits in relation to position of saibo cutting on the mantle of black-lipped pearl oyster Pinctada margaritifera

Abstract: Cultured pearl production from Pinctada margaritifera uses the biomineralization capacities of the mantle graft, the saibo, which is usually obtained from only the middle mantle section of the donor oyster. To evaluate the potential for using other parts of the mantle, this study explores and describes the cultured pearl quality traits, pearl size, shape, surface defects and colour parameters obtained with saibo from the entire length of the mantle, comprising the four following sections: 1) posterior, 2) conn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A considerable number of studies have focused on the identification of genes involved in aragonite and/or calcite formation in pearl oyster species and other bivalves capable of shell mineralisation [20, 22, 46, 47, 48–54]. Nonetheless, it has proven difficult to extrapolate the role of key actors involved in determining cultured pearl quality across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of studies have focused on the identification of genes involved in aragonite and/or calcite formation in pearl oyster species and other bivalves capable of shell mineralisation [20, 22, 46, 47, 48–54]. Nonetheless, it has proven difficult to extrapolate the role of key actors involved in determining cultured pearl quality across studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in P. margaritifera , based on controlled bi-parental crosses and the F1 generation, demonstrated heritability ( h 2 from 0.21 to 0.37) for nacre weight and thickness, pigmentation darkness and colour, surface defects and grade, signifying a donor oyster effect with a genetic basis, although there were also important interaction components [10]. Previous studies reported that location, temperature and food availability [1113], pearl rotation [14], donor oyster genotype [4, 9, 1518], age [19], position of graft mantle [20] and contamination during the graft operation and/or graft operator skills [21] are all determinants of final pearl quality and do not necessarily affect similar traits.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of P. margaritifera to produce pearl colours overlapping the colour ranges of pearls of two other rival species is related to donor shell phenotypic diversity. This donor influence is observed not only at an inter-individual scale 13 but also at an intra-individual level, through effects of the position on the donor mantle at which the graft is cut 14 .…”
Section: Introductionmentioning
confidence: 99%